Pengaruh Perilaku Keuangan, Kontrol Diri, dan Skala Pengetahuan Keuangan Digital (DFKS) terhadap Perilaku Menabung Mahasiswa Perantau Jurusan Manajemen Universitas Palangka Raya - Marsha Denanda Putri; Rita Sarlawa; Ronni Haga; Evinalia Yeba (SAFE-Network, 2026)
This study aims to analyze the effect of financial behavior, self-control, and Digital Financial Knowledge Scale (DFKS) on the saving behavior of overseas students majoring in Management at Palangka Raya University. The research employs a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS) samples were selected using a proportional stratified random sampling technique, yielding 171 respondents from a total population of 300 overseas students, and data were collected through a questionnaire employing a 1-5 Likert scale. The results indicate that financial behavior has a positive and significant effect on saving behavior, self-control, has the stronger influence on saving behavior and (DFKS) also demonstrate a positive and significant effect. The three variables simultaneously explain 80,4% of the variance in saving behavior (R2 = 0,804). These findings confirm the Theory of Planned Behavior (TPB) framework, where attitude (financial behavior) perceived behavioral control (self-control), and external supporting factor (Digital Financial Knowledge Scale) collectively contribute to actual saving behavior. This study recommends integrating personal financial management and digital financial literacy materials into the curriculum, as well as organizing regular seminars for overseas students.